2013
DOI: 10.1673/031.013.11701
|View full text |Cite
|
Sign up to set email alerts
|

Altitudinal and Seasonal Variation inDrosophilaSpecies on Mount Japfu of Nagaland, a Sub-Himalayan Hilly State of India

Abstract: Drosophila (L.) (Diptera: Drosophilidae) has richly contributed to the understanding of patterns of inheritance, variation, speciation, and evolution. Drosophila, with its cosmopolitan nature and complexities in species compositions, is an excellent model for studying the eco-distributional patterns of various species. This study analyzed the altitudinal and seasonal variation in Drosophila species of Mount Japfu in Nagaland, a sub-Himalayan hilly state of northeast India, over the course of one year. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Although seasonal fluctuations in tropical regions are not as drastic as in other latitudes, climatic changes due to seasonality can also affect insect abundance and diversity in the tropics [ 7 ], particularly because of seasonal differences in precipitation [ 11 , 13 ]. For example, Achumi et al [ 11 ] showed a positive correlation of Drosophila fly population density with rainfall. Still, this is not true for all dipterans because several species of flies respond differently to seasonal variation [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although seasonal fluctuations in tropical regions are not as drastic as in other latitudes, climatic changes due to seasonality can also affect insect abundance and diversity in the tropics [ 7 ], particularly because of seasonal differences in precipitation [ 11 , 13 ]. For example, Achumi et al [ 11 ] showed a positive correlation of Drosophila fly population density with rainfall. Still, this is not true for all dipterans because several species of flies respond differently to seasonal variation [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Environmental conditions associated with higher elevation are known to influence insect communities [1]. For example, it is widely accepted that there is a decrease in the abundance and diversity of many insect groups at higher elevations, including beetles (Coleoptera) [2][3][4][5], moths and butterflies (Lepidoptera) [6][7][8], wasps (Hymenoptera) [9,10], and flies (Diptera) [1,11,12]. In addition, insect communities change according to season.…”
Section: Introductionmentioning
confidence: 99%
“…However, the Drosophila diversity is least influenced simply by species richness. (Torres andMadi-Ravazzi 2006 andAchumi et al, 2013). The dominance recorded for the total taxa of six at 0.3464 in the monsoon.…”
Section: Discussionmentioning
confidence: 96%
“…In this region, researchers have extensively studied the effect of several factors such as precipitation, temperature, humidity, habitat, habitat loss, and global warming, with pioneering survey by Dobzhansky and Pavan (1950) from Brazil and subsequent studies by other researchers such as Benado & Brncic (1994) in forests of Chile, other localities of Brazilian forests (De Toni & Hofmann, 1995;Martins, 2001;Tidon, 2006;Torres & Madi-Ravazzi, 2006;Mata et al, 2008;Gottschalk et al, 2008;Schmitz et al, 2007Schmitz et al, , 2010De Toni et al, 2007;Bizzo et al, 2010;Poppe et al, 2012Poppe et al, , 2014Penariol & Madi-Ravazzi, 2013;Garcia et al, 2014;Cavasini et al, 2014;Monteiro et al, 2016;Oliveira et al, 2016;Coutinho-Silva et al, 2017;Duarte et al, 2018). Population assemblage of Drosophilidae from India are poorly understood (Hegde et al, 2001), except few studies (Guruprasad et al, 2010;Achumi et al, 2013;Srinath & Shivanna, 2014b). All these studies have analysed drosophilid population with respect to variations in temperature, rainfall, seasons, and altitude.…”
Section: Introductionmentioning
confidence: 99%